Magnetic resonance imaging sequence evaluation of an MR Linac system; early clinical experience. (December 2019) - Eccles, C.L.; Adair Smith, G.; Bower, L.; Hafeez, S.; Herbert, T.; Hunt, A.; McNair, H.A.; Ofuya, Mercy; Oelfke, Uwe; Nill, Simeon; Huddart, R.A.; ,
Highlights: Selection of MRI sequences for use in MRI-guided radiotherapy by end-users. T2w images were preferred in the pelvis, abdomen and head & neck regions. T1w images were preferred in the thorax. Abstract: Objective(s): To systematically identify the preferred magnetic resonance imaging (MRI) sequences following volunteer imaging on a 1.5 Tesla (T) MR-Linear Accelerator (MR Linac) for future protocol development. Methods: Non-patient volunteers were recruited to a Research and Ethics committee approved prospective MR-only imaging study on a 1.5T MR Linac system. Volunteers attended 1–3 imaging sessions that included a combination of mDixon, T1w, T2w sequences using 2-dimensional (2D) and 3-dimensional (3D) acquisitions. Each sequence was acquired over 2–7 minutes and reviewed by a panel of 3 observers to evaluate image quality using a visual grading analysis based on a 4-point Likert scale. Sequences were acquired and modified iteratively until deemed fit for purpose (online image matching or re-planning) and all observers agreed they were suitable in 3 volunteers. Results: 26 volunteers underwent 31 imaging sessions of six general anatomical regions. Images were acquired in one or two of six general anatomical regions: male pelvis (n = 9), female pelvis (n = 4), chestwall/breast (n = 5), lung/oesophagus (n = 5), abdomen (n = 3) and head and neck (n = 5). Images were acquired using a pre-defined exam-card that on average, included six sequences (range 2–10), with a maximum scan time of approximately one hour. The majority of observers preferred T2-weighted sequences. The thorax teams were the only groups to prefer T1-weighted imaging. Conclusions: An iterative process identified sequence agreement in all anatomical regions. These sequences will now be evaluated in patient volunteers. Advances in knowledge: This manuscript is the first publication sharing the results of the first systematic selection of MRI sequences for use in on-board MRI-guided radiotherapy by end-users (therapeutic radiographers and clinical oncologists) in healthy volunteers.